Ambienti digitali ed extended reality: alcune questioni semiotiche a partire da esempi di branding e retailing - Ventura Bordenca, Ilaria (E|C, 2021)
This article raises some semiotic questions about extendend reality that involves the wide range of digital technologies including VR (virtual reality), AR (augmented reality) and MR (mixed reality), drawing on some cases from the world of organised retail and branding. We are talking about a set of technologies that, since the beginning of their creation and today in the fields in which they are most used, have brought to the surface, because they have questioned them, a series of theoretical problems of great interest for semiotics, such as corporeality and perception, the situation of fruition and the change of point of view, but also the narrative dimension produced - or not produced - by these technologies. Our aim is to highlight some salient points of the phenomenon of immersive technologies that are relevant for a semiotic analysis and for their theoretical debate, asking ourselves what what research areas they may open up.